2013
DOI: 10.1177/160940691301200117
|View full text |Cite
|
Sign up to set email alerts
|

Data Display in Qualitative Research

Abstract: Visual displays help in the presentation of inferences and conclusions and represent ways of organizing, summarizing, simplifying, or transforming data. Data displays such as matrices and networks are often utilized to enhance data analysis and are more commonly seen in quantitative than in qualitative studies. This study reviewed the data displays used by three prestigious qualitative research journals within a period of three years. The findings include the types of displays used in these qualitative journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 20 publications
0
83
0
2
Order By: Relevance
“…We used culturally-relevant visual imagery to map out how each of these concepts related to one another on various spatial and temporal scales (Figure 3.3). Use of visual metaphor allows for an organized structuring of data enhanced through multiple levels of representation and meaning (Verdinelli & Scagnoli, 2013). Through each phase of the research process we observed our collective story of survival, adaptation and resilience unfolding.…”
Section: Findings and Discussion: Unfolding Our Collective Story Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…We used culturally-relevant visual imagery to map out how each of these concepts related to one another on various spatial and temporal scales (Figure 3.3). Use of visual metaphor allows for an organized structuring of data enhanced through multiple levels of representation and meaning (Verdinelli & Scagnoli, 2013). Through each phase of the research process we observed our collective story of survival, adaptation and resilience unfolding.…”
Section: Findings and Discussion: Unfolding Our Collective Story Of Smentioning
confidence: 99%
“…Prior to the workshop, we worked with a local artist and Indigenous scholar to visualize our data. Use of visual metaphor can enhance data through drawing together multiple levels of meaning (Verdinelli & Scagnoli, 2013). We drew from Jibaro and Indigenous Caribbean language and visual symbols to identify cultural visual metaphors that hold relevance within the local community context.…”
Section: Reciprocity: Ensuring Benefit To Communitymentioning
confidence: 99%
“…Nvivo version 10 was used for coding and managing data analysis. Data were analysed using thematic data analysis techniques and presented as thematic syntheses and an illustrative visual display [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…The results from the content analysis are visualized using a bar graph and a dendrogram, which is a popular method to display hierarchical clustering of similar objects into groups (Henry et al, 2015). Although such visual displays are common in quantitative research (Verdinelli & Scagnoli, 2013), some studies have suggested using them to illustrate thematic qualitative information as well (see for example, Guest & McLellan, 2003;Stokes & Urquhart, 2013). While the data does not need to be originally quantitative, the methods necessitate some kind of data quantification.…”
Section: The Ethical Dimensions Of Public Opinion On Smart Robotsmentioning
confidence: 99%